2022
DOI: 10.1017/s1759078722000174
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to non-invasive blood glucose sensing based on a single-slot defected ground structure

Abstract: In this study, we explore a novel approach to measure blood glucose concentration in a non-invasive way using a compact defected ground structure (DGS) filter. The proposed sensor is promising because it is cost-effective, compact, non-ionizing in nature, and convenient for diabetics. Therefore, a portable microwave biosensor can be utilized using these features. In this study, we present a single DGS sensor which is designed on a Rogers RO4003C substrate and fed by a 50 Ω microstrip line, and operating in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…PPG absorbance and reflectance signal can vary depending on blood circulation, blood viscosity, peripheral vascular resistance, vascular elasticity, and movement [37]. To increase the accuracy of this technique, machine learning or other paired sensor techniques would be needed to adjust for these variables [40].…”
Section: Photoplethysmography (Ppg)mentioning
confidence: 99%
See 1 more Smart Citation
“…PPG absorbance and reflectance signal can vary depending on blood circulation, blood viscosity, peripheral vascular resistance, vascular elasticity, and movement [37]. To increase the accuracy of this technique, machine learning or other paired sensor techniques would be needed to adjust for these variables [40].…”
Section: Photoplethysmography (Ppg)mentioning
confidence: 99%
“…Research has shown promise for glucose monitoring handheld devices for in vivo mmW measurements through the earlobe or finger web between 3 and 5 mm thick using silicon-loaded probes [105], through a compact finger slot reader or fingertip [40,96], and through the forearm [using bioheat transfer models;] [106], [using a near-field probe;] [107]. The studies reported that skin, fat, and blood have the most significant impact on the reflected signal, while muscle and bone have a negligible effect [107].…”
Section: Millimeter Waves and Microwaves (Mmw/mws)mentioning
confidence: 99%
“…Several studies have investigated the impact of dielectric constant on the sensitivity of noninvasive blood glucose detection. In a comparative study 1 , researchers evaluated different substrates and discovered a positive correlation between higher dielectric constants and improved sensitivity and accuracy in glucose detection. Similarly, in related research 2 , experiments using diverse substrates demonstrated that higher dielectric constants contributed to enhanced glucose detection capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The sensors with high sensitivity can be used for adjustable cancellation [57]. The important issue is what methods and techniques are needed to increase the sensitivity of sensors [58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%